Kaji Eksperimental Turbin Air Darrieus Tipe-H Menggunakan Blade Hydrofoil Standar Naca 2415 - Rudi Kusuma Wijaya; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
An experimental review of the H-type Darrieus water turbine has been carried out using a standard NACA 2415 hydrofoil blade to determine the static and dynamic torque values produced by the 3-blade and 6 blade Darrieus hydro-turbine turbines. mx 0.6 m x 1 m. This test uses a variation of three blades and six blades, with turbine diameter 0.44 m x 0.15 m on the outer turbine and 0.18 x 0.14 m on the inner turbine and 0.10 m chord length with variations of the angle of attack from 0º to 360º, using variations in the speed of the first water flow 0.3 m / s and the variation of the second water flow velocity is 0.65 m / s. At a water speed of 0.3 m / s six blades, the static torque value generated is 0.3 Nm, the dynamic torque value is 0.384 Nm, at a water speed of 0.65 m / s the dynamic torque value is 0.432 Nm and the static torque value is 0.384 Nm, for Darrieus turbine testing three blades with a water flow velocity of 0.3 m / s dynamic torque value is 0.336 and with the same speed its static torque is 0.264 Nm. At the water velocity of 0.65 m / s, the dynamic torque value is 0.384 Nm, and the static torque value is 0.336 Nm. From the measurement data it can be concluded that the variation of the six blade turbine has a value of static torque and dynamic torque higher than the three blade turbine, the number of blades greatly influences the kinetic energy absorption of water to be converted into static and dynamic torque.Keywords: Turbine Darrieus, static torque, dynamic torque